Semi-supervised learning advances species recognition for aquatic biodiversity monitoring - Ma, Dongliang; Wei, Jine; Zhu, Likai; Zhao, Fang; Wu, Hao; Chen, Xi; Li, Ye; Liu, Min (Frontiers in Marine Science, 2024)
Aquatic biodiversity monitoring relies on species recognition from images. While deep learning (DL) streamlines the recognition process, the performance of these method is closely linked to the large-scale labeled datasets, necessitating manual processing with expert knowledge and consume substantial time, labor, and financial resources. Semi-supervised learning (SSL) offers a promising avenue to improve the performance of DL models by utilizing the extensive unlabeled samples. However, the complex collection environments and the long-tailed class imbalance of aquatic species make SSL difficult to implement effectively. To address these challenges in aquatic species recognition within the SSL scheme, we propose a Wavelet Fusion Network and the Consistency Equilibrium Loss function. The former mitigates the influence of data collection environment by fusing image information at different frequencies decomposed through wavelet transform. The latter improves the SSL scheme by refining the consistency loss function and adaptively adjusting the margin for each class. Extensive experiments are conducted on the large-scale FishNet dataset. As expected, our method improves the existing SSL scheme by up to 9.34% in overall classification accuracy. With the accumulation of image data, the improved SSL method with limited labeled data, shows the potential to advance species recognition for aquatic biodiversity monitoring and conservation.